(untitled) (The Review of Diabetic Studies, 2024)
A combination of reasons, such as an aging population, rising healthcare demand, and a dearth of adequate educational and training programs, are contributing to Saudi Arabia’s severe nursing manpower deficit. cultural views of Recruitment attempts have been hampered by the nursing profession and competitive pay in other industries. The personnel dilemma is made worse by the current workforce’s high turnover rates and burnout, which are frequently caused by overwork. Additionally, the quality of care and patient safety have been compromised since the quick growth of healthcare facilities—especially in urban areas—has not been accompanied by an increase in the number of skilled nursing staff. Present study evaluates the scenario in terms of secondary data, the studies are taken from 2010 to 2021.